An Improved CPU Time in Triangle Splitting Method for Solving a Biobjective Mixed Integer Program - Al-Hasani, Ali; Al-Rabeeah, Al-Rabeeah; Kumar, Santosh; Eberhard, Andrew (International journal of mathematical, engineering and management sciences, 2018)
In this paper, an existing algorithm known as Triangle Splitting Method (TSM) for the Bi-Objective Mixed Integer Program (BOMIP) has been modified, which has been named “An Improved Triangle Splitting Method (ITSM)”. The TSM solves many unnecessary single objectives Mixed Integer Programs (MIP) to split each triangle with two rectangles, and second, it doesn’t find the all efficient frontiers. The proposed ITSM has resulted in redaction of CPU time by solving one MIP at each triangle and finds more number of nondominated frontiers compared to the TSM. The proposed modification has been tested in many instances.